Base temperature for a phenological stage in plum cultivar Horvin (Prunus salicina Lindl.) - Orjuela-Angulo, Mayerlin; Parra-Coronado, Alfonso; Camacho-Tamayo, Jesús Hernán (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
The plum (Prunus salicina Lindl.) is affected by the amount of water provided by its environment, as conditioned by climatic factors, especially temperature. Fruit development, in terms of physiological time or growing degree-days (GDD), is more accurate than quantification in terms of crop scheduling dates. The objective of this research was to determine the base temperature (Tb) of the phenological period between fruit set and harvest in Horvin plums and to express this duration in terms of GDD to determine the harvest date. Twenty trees were marked per locality at four different altitudes (2,449; 2,285; 2,215 and 2,195 m) in the municipality of Nuevo Colon, Boyaca. During 2015 and 2016, the dates of fruit set and harvest were recorded. Tb was estimated using different methods, as well as the GDD required to go from fruit set to harvest. The variance showed the best statistical fit between coefficient of variation and standard deviation for estimating Tb, with a high degree of correlation. The Tb for this phenological period was 2.9ºC. The results showed that a mean of 1,528 GDD and 81 days were required to pass from fruit set to fruit harvest.